WAYANG WAHYU "MUSA THE LIBERATOR": INCULTURATION OF FAITH AND CULTURE IN FOSTERING A SENSE OF NATIONALISM: WAYANG WAHYU “MUSA SANG PEMBEBAS”: INKULTURASI IMAN DAN BUDAYA DALAM ‎MENUMBUHKAN RASA NASIONALISME - Jaka Rianto; Seruni Widawati (SOSIOEDUKASI, 2025)
Wayang Wahyu play "Musa Sang Pembebas" is a form of inculturation of the Catholic faith and Javanese culture through puppet performance. The story of Moses from Exodus 14:15–15:1 was adapted as a symbol of liberation and the spirit of nationalism. This performance involved the students of SMP PL Bintang Laut Surakarta and was innovatively packaged with Indonesian, gamelan, dance, and theater so that it was easy for the younger generation to understand. This study uses an aesthetic reception approach with the method of sanggit and pakeliran.The results show that the proclamation of faith through local cultural media can strengthen religiosity, foster nationalism, and strengthen the attachment of the younger generation to cultural heritage. This work reflects the spirit of "100% Catholic, 100% Indonesian" as a form of synergy of faith and love for the homeland.